Food safety curriculum guide for Filipino Junior High school students - Limon, Mark Raguindin; Chua, Consuelo T.; Gabriel, Alonzo A.; Calingasan, Lorina Y. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (Ph.D. Home Economics)--University of the Philippines Diliman
Keywords: Education -- Curricula -- Philippines; Education, Secondary -- Curricula -- Philippines; Food security -- Philippines